Shear lag Phenomenon in High Rise Structures - Singh, Gyani Jail (IIT(BHU), Varanasi, 2015)
Abstract is available in the attachment.
This thesis submitted by PhD. Scholar IIT(BHU), Varanasi. & supervised by Dr. Rajesh Kumar & Dr. S. Mandal.
Keywords: Shear Lag; Phenomenon; HIgh Rise Structures